Comparative Analysis of One-Stage versus Two-Stage Brachio-Basilic Arteriovenous Fistulas - Saklayen, S M G; Nuzhat, Rusama; Polash, Wahidul Azad; Zahan, Laila Akter; Talukdar, Peyali; Eva, Khadiza Rahmam (Bangladesh Medical Journal, 2025)
Brachio-basilic arteriovenous fistulas (BBAVFs) are a preferred vascular access option for hemodialysis in patients with end-stage renal disease (ESRD) when the cephalic vein is unsuitable. Both the one-stage and two-stage BBAVF techniques offer distinct advantages and are widely practiced, but their comparative outcomes remain under debate. This study aims to compare the clinical outcomes of one-stage versus two-stage BBAVF creation in patients with ESRD. This prospective, randomized interventional study was conducted at the Vascular Surgery Department of Ibrahim Cardiac Hospital & Research Institute, Dhaka, from January 2021 and June 2024. A total of 64 ESRD patients who met the inclusion criteria were randomly assigned into two equal groups (n = 32 each) to undergo either one-stage or two-stage BBAVF creation. Preoperative evaluations included clinical assessment, laboratory tests, and duplex ultrasonography. The outcomes assessed included primary and secondary patency, complication rates, early postoperative discomfort, and vascular parameters, with consideration of baseline characteristics. Baseline characteristics were comparable between the two groups. The two-stage group demonstrated significantly higher primary patency (96.9% vs. 81.3%; p = 0.045), while secondary patency rates were identical (90.6%) in both groups. However, the two-stage technique was associated with significantly higher rates of venous hypertension (p = 0.020) and steal syndrome (p = 0.039). Early postoperative pain was significantly lower in the one-stage group (p = 0.001). No significant differences were found between the groups regarding postoperative vein diameter, depth, or volume flow. Although the two-stage BBAVF technique offers superior primary patency, it carries a higher risk of complications. In contrast, the one-stage approach provides comparable long-term outcomes with less early postoperative pain. These findings highlight the need to individualize the choice of technique based on patient anatomy, comorbidities, and surgical expertise. Bangladesh Med J. 2024 May; 53(2): 1-7